UJI AKTIVITAS ANTIOKSIDAN DAUN KERSEN (Muntingia calabura L.) DENGAN METODE DPPH (1,1-difenil-2-pikrilhidrazil) DAN FRAP (Ferric Reducing Antioxidan Power) - Fitriyanti Jumaetri Sami; Syamsu Nur; Naimah Ramli; Budi Sutrisno (As-Syifaa Jurnal Farmasi, 2017)
Has conducted research of antioxidant activity from kersen leaves (Muntingia calabura Linn) using DPPH (1,1-diphenyl-1-picrilhydrazil) and FRAP (Ferric Reducing Antioxidant Power). Kersen leaves extracted by maceration using ethanol 70%. Phytochemical identification of kersen leaves contain phenolic, flavonoids and saponins compounds. The test results of antioxidant activity using DPPH method with series concentrations of 2, 4, 6, 8, and 10 ppm obtain IC50 value 6.8249 ug / ml. Testing of the ethanol extract of antioxidants obtained by FRAP method IC50 83,149 µM. Based on these data the ethanol extract of kersen leaves has good antioxidant activity.